Answer:
a) sample of size n from the population has an equal chance of being selected.
b) Every member of the population has an equal chance of being included in the sample.
Step-by-step explanation:
Simple random sampling:
- It is a type of probabilistic sampling.
- It is an unbiased representation of population.
- The probability of selection is equal for every observation.
- A sample is taken in such a way that each member has an equal probability of being selected.
- A simple random sample is a subset of a statistical population in which each member of the subset has an equal probability of being chosen.
- Thus,the correct interpretation is given by,
a) sample of size n from the population has an equal chance of being selected.
b) Every member of the population has an equal chance of being included in the sample.
- c) The simplest method of selection is used to create a representative sample.
The statement is false.
There is no pattern or technique used for selection. The selection is purely random.
- d) Each subset of the population has an equal chance of being included in the sample.
The statement is false.
Each object of the population has an equal chance of being included in the sample. and not each subset.
- e) Every sample of size n from the population has a proportionally weighted chance of being selected.
The given statement is false.
To evaluate the combination we proceed as follows:
21C3
Given nCk we shall have:
n!/[(n-k)!k!]
thus plugging the values in the expression we get:
21!/[(21-3)!3!]
=21!/(18!×3!)
=1330
Answer: 1330
Answer:
(8, -5); x=8; y=-5
Step-by-step explanation:
i'll be solving via substitution
2x+3y=1; y=-2x+11
2x + 3(-2x +11) = 1
2x -6x +33 = 1
-4x = -32
x = 8
2(8) + 3y = 1
16 + 3y = 1
3y = -15
y = -5
(8, -5)
Check:
-5 = -2(8) + 11
-5 = -16 + 11
-5 = -5
Answer:
0 solutions
Step-by-step explanation:
4(x-2)=4x+10
4x-8 = 4x+ 10
-8 = 10 (not true)
(When you have something like 6=7, 0 solutions. If it is like 6=6, infinite solutions. x=6, one solution)
(2x + 2) = (3x + -52)
Reorder the terms:
(2 + 2x) = (3x + -52)
Remove parenthesis around (2 + 2x)
2 + 2x = (3x + -52)
Reorder the terms:
2 + 2x = (-52 + 3x)
Remove parenthesis around (-52 + 3x)
2 + 2x = -52 + 3x
Solving
2 + 2x = -52 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
2 + 2x + -3x = -52 + 3x + -3x
Combine like terms: 2x + -3x = -1x
2 + -1x = -52 + 3x + -3x
Combine like terms: 3x + -3x = 0
2 + -1x = -52 + 0
2 + -1x = -52
Add '-2' to each side of the equation.
2 + -2 + -1x = -52 + -2
Combine like terms: 2 + -2 = 0
0 + -1x = -52 + -2
-1x = -52 + -2
Combine like terms: -52 + -2 = -54
-1x = -54
Divide each side by '-1'.
x = 54
Simplifying
x = 54